The Relationship Between Principals’ Leadership Styles and Teachers Commitment in Secondary Schools of East Shoa Zone - Fikadu Ereso (My University, 2015)
The main purpose of this study was toassess the commonly practiced leadership stylesand investigate the relationship between principals’ leadership styles (transactional, transformational, and laissez-faire) and teachers’ commitments (affective, continuance, and normative commitment) in Secondary Schools of East Shoa Zone of Oromia Regional State, in Ethiopia.Total participants in the research were 110, included 94 teachers and 16 principals, with a non response rate of 13.3% from 6 secondary schools of East Shoa, Oromia Region. Correlational descriptive survey research designwas used. Two separate instruments, namely Multifactor Leadership Questionnaire (MLQ) and Organizational Commitment Questionnaire (OCQ), were used to measure principals’ leadership styles and teachers’ commitment respectively. The obtained quantitative data were processed using SPSS (Version 20) and descriptive statistics like frequency, percentage, mean and standard deviation. The findings of the study revealed that most of the principals found in East Shoa, Zone of Oromia Regional State, adopt from most to least, Laissez-faire, Transactional and Transformational Leadership Styles, principals Transformational Leadership style has significant and positive correlations with affective and continuance teachers commitments while principals transactional leadership style has significant and positive correlation with only normative commitment. The principals’ laissez-faire leadership style was found to be significantly and negatively associated with teachers’ affective commitment. Finally, based on the findings of the study, recommendations like enhancinginteraction of principals’ transformational and transactional leadership styles in affecting attitudes towards commitment to the school andprincipals of secondary schools needs to pay more attention in developing efficient team work and express warm concern and trust to teachers through transformational leadership styles were recommended.
Keywords: Educational Planning